THE INFLUENCE OF ORGANIC FERTILIZER (POTASSIUM HUMATE) ON THE GENETICS, PHENOTYPIC VARIATIONS, AND HERITABILITY OF WHEAT VARIETIES - O. H. Al-Rawi; M. A. Hamed; A. A. Bedn; N. H. Khalaf (مجلة الأنبار للعلوم الزراعية)
This field experiment was conducted during the winter season of 2022-2023 in a community located south of Fallujah, Al-Anbar, Iraq and involved the use of seeds from five different wheat varieties, namely Mahmoudia, Diyar, Wafiyya, Edna 99, and Rashid. The seeds were treated with 1000, 2000, and 3000 gm.h-1 of potassium humate 90% fertilizer. Data analysis showed significant differences across all variables and treatments. The genetic variance was found to be greater than the environmental variance for all tested variables, and this difference increased with higher levels of humic fertilizer. However, in the case of leaf area, genetic variance decreased with higher amounts of humic fertilizer. The number of spikes per square meter exhibited the highest broad-sense heritability (0.958) at the 2000 gm.ha-1 level of humic fertilizer. This was followed by the number of grains per spike with a heritability of 0.909 at the 3000 gm.ha-1level. The standard coefficient and genetic variance values varied depending on the amount of humic fertilizer applied, resulting in increased grain yield, number of grains per spike, and number of spikes per square meter.